The Effect of Quiz Team Type Active Learning Methods on Student Learning Motivation - Maulia, Rinda Arni; Okon, Cecilia (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this study was to determine the effect of using the quiz team type active learning method on student motivation. Methodology: This type of research is experimental research with a quantitative research approach. The population determined by the researcher was class VII junior high school students. The technique for determining the sample in this study was to use a purposive sampling technique. The data collection instruments used were questionnaires and documentation. Data were analyzed using normality, homogeneity and hypothesis tests. Main Findings: The results of this research are that the average learning motivation for Pancasila and Citizenship Education (PPKn) of experimental class students taught using the Quiz Team Active Learning Method is 83.166, which is higher than the average learning motivation for the control class which applies the Conventional Method, namely 45.533. Apart from that, there is a significant influence of the Quiz Team Type Active Learning Method in the subject of Pancasila and Citizenship Education (PPKn) on the learning motivation of class VII junior high school students. Novelty/Originality of this study: This research can answer the problems faced by students, namely the lack of maximum student motivation in the Pancasila and Citizenship Education (PPKn) learning process.